Better Brain and Cognition Prior to Surgery Is Associated With Elevated Postoperative Brain Extracellular Free-Water in Older Adults - Tanner, Jared J.; Amin, Manish; Hardcastle, Cheshire; Parvataneni, Hari; Vaillancourt, David E.; Mareci, Thomas H.; Price, Catherine C. (Frontiers in Aging Neuroscience, 2019)
For adults age 65 and older, the brain shows acute functional connectivity decreases after total knee arthroplasty with the severity of change predicted by preoperative cognitive function and brain disease burden. The extent of acute structural microstructural brain changes acutely after surgery remains unknown within the literature. For the current study, we report on the severity of acute post-surgery microstructural brain changes as measured by diffusion imaging and free-water analysis. Participants who underwent total knee arthroplasty under general anesthesia and non-surgery peers were part of a federally funded prospective cohort investigation involving participants. Recruitment occurred between 2013 – 2017. Data were collected in outpatient and inpatient settings within a university-affiliated medical center. A total of 232 TKA patients were referred by the study surgeon and contacted for study inclusion. Of these, 78 met inclusion and exclusion criteria and completed assessment. Five participants were excluded due to anesthetic protocol changes (spinal instead of general) with an additional 12 excluded for imaging-related complications. The total included sample size was 61. A total of 127 non-surgery participants were screened with 66 enrolled. One non-surgery participant was excluded for an imaging-related complication. Total knee arthroplasty and general anesthetic protocols were standardized. Participants received preoperative neurocognitive assessment and brain magnetic resonance imaging, with repeat imaging 48 hours after surgery or pseudosurgery. Free-water analyses were performed using diffusion weighted images and tract-based spatial statistics with baseline cognitive data used to predict free-water changes. Surgery participants had widespread increases in white matter free-water. Surgery participants with higher cognitive functions as measured by immediate memory and less evidence of brain atrophy and disease (i.e., brain integrity) had greater free-water increase. Non-surgery peers had no free-water change. We interpret the surgery group’s free-water change as indicating widespread brain white matter glial response, with greater change indicative of better brain response to the acute surgery/anesthesia experience.